Cfd Applied in the Optimization of A Dryer For Parchment Coffee Drying (Coffeaarabica L.) By Forced Ventilation - Salazar Esquivel, Randall (2018)
The present study analyzes the efficiency of parchment coffee drying process in a forced greenhouse type solar dryer. The environmental conditions in the solar dryer were measured during a day of operation, in which the air is introduced to the dryer by means of two driving fans and leaves the other side, with two extractor fans. A numerical model was established that allowed to replicate the internal environmental conditions of the dryer through software Fluent® de ANSYS Workbench. The air flow inside the dryer presents a laminar behavior, being little beneficial for coffee drying. It was proposed to introduce diffusers inside the dryer, which, through the simulation, proved to be effective in generating a more turbulent flow, which increases the effectiveness in the process of removing moisture from the coffee in the dryer